Effects of pin fins and vortex generators on thermal performance in a microchannel with Al2O3 nanofluids. (15th January 2022) - Wang, Jin; Yu, Kai; Ye, Mingzheng; Wang, Enyu; Wang, Wei; Sundén, Bengt
Abstract: This paper performs a comparative analysis to obtain the optimal cross-section shape and parameters of both pin fins and vortex generators. A novel combined structure with pin fins and vortex generators is proposed to enhance thermal performance of an integrated microchannel heat sink. Effects of nanoparticle diameter and volume fraction are investigated using Al2 O3 nanofluid and DI-water as working fluid. Pin fins and vortex generators cause enhancements of flow disturbance and heat transfer on microchannel heat sinks. Results indicate that oval pin fins have better improvements of thermal/hydraulic performance compared to round and diamond pin fins. The oval pin fin with 0.4 mm spacing and 0.1 mm height presents the highest overall performance factor in the Reynolds number range of 340–640. Presence of vortices intensifies the mixing of the hot fluid near bottom surface and cold fluid near top surface. The optimal vortex generator with length of 0.08 mm and height of 0.06 mm provides a 30% increase in overall performance factor compared to the rectangular microchannel at Reynolds number of 340. Mechanism of heat transfer enhancement is analyzed by investigating flow velocity, temperature distribution and field synergy angle distribution in microchannels. Based on the field synergy principle, it is found that a small and uniformly distributed synergy angle is achieved in the integrated microchannel. According to comparisons of the overall performance factor and total thermal resistance, the optimal nanoparticle diameter and Al2 O3 volume fraction of nanofluids are 20 nm and 4%, respectively. Highlights: Performance of microchannel is improved by changing structures and working fluids. There is 15.7% increase of the overall performance by pin fins with optimal parameters. Vortex generators intensify fluid mixing and secondary flow to achieve 30% increase. Synergy angles become smaller and uniformly distributed in integrated microchannel. Nanofluid with 20 nm particle diameter and 0.04 vol fraction is optimal choice.